Immune imbalance in the pre-ovulatory follicular microenvironment of overweight and obese women during IVF - Yang Liu; Yiran Zhao; Chengliang Zhou; Hong Zhu; Jiexue Pan; Jing Fu; Hefeng Huang; Hui Lin; Li Jin (Journal of Ovarian Research)
Abstract Background Overweight and obesity can induce an inflammatory milieu in the oocyte microenvironment and are closely associated with reduced assisted reproductive outcomes. Objective How are immune cells, cytokines and lipid profiles altered in the pre-ovulatory microenvironment of overweight and obese women? Methods 32 women undergoing in vitro fertilization (IVF) were included, with 14 overweight or obese (OW) and 18 normal weight (NW) participants. Serum was collected before ovulation induction, follicular fluid (FF) and aspirates were obtained during oocyte retrieval for flow cytometry, cytokines, hormone, and lipid profiles measurement. Clinical outcomes were recorded through a one-year follow-up. Results The percentage of T cells in the pre-ovulatory follicular microenvironment, especially CD4+ T cells, increased significantly in the OW group, which positively related with BMI. Notably, type 2 cytokine IL4 and IL13 transcription level in OW group had significantly increased, while the type 1 cytokine IFNG only showed a non-statistically significant upward trend. Lipid profiles were screened, revealing no difference between the two groups, however, levels were higher in serum compared to FF. Additionally, the concentration gradient of TG between serum and FF was 22-fold in OW group (2.92 ± 3.66 vs. 0.13 ± 0.03), which was significantly higher than the 12-fold gradient observed in NW group (1.72 ± 0.95 vs. 0.14 ± 0.08). Furthermore, day 3 high quality embryos rate is negatively associated with BMI and exhibits a decreasing trend in OW group. Conclusion Overweight and obesity can disrupt immune hemostasis in the pre-ovulatory follicular microenvironment, potentially leading to adverse effects on assisted reproductive outcomes.